2017
DOI: 10.1186/s12876-017-0726-2
|View full text |Cite
|
Sign up to set email alerts
|

Upcoming pharmacological developments in chronic hepatitis B: can we glimpse a cure on the horizon?

Abstract: BackgroundHepatitis B virus (HBV) chronic infection affects up to 240 million people in the world and it is a common cause of cirrhosis and hepatocellular carcinoma (HCC). HBV covalently closed circular DNA (cccDNA) plays an essential role in HBV persistence and replication. Current pharmacological treatment with nucleos(t)ide analogues (NA) may suppress HBV replication with little or no impact on cccDNA, hence lifelong treatment is required in the vast majority of patients. Clearances of intrahepatic cccDNA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 91 publications
1
17
0
Order By: Relevance
“…On the other hand, Birinapant and Dynasore from the category of the antiviral drug show a good binding affinity towards SARS-CoV-2 M pro . Antiviral activity of Birinapant against chronic hepatitis B virus (HBV) infection by induction of apoptosis by inhibiting cellular inhibitor of apoptosis proteins (cIAPs) has been reported in the literature (Alonso et al., 2017 ; Ebert et al., 2015). The second antiviral lead compound i.e.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Birinapant and Dynasore from the category of the antiviral drug show a good binding affinity towards SARS-CoV-2 M pro . Antiviral activity of Birinapant against chronic hepatitis B virus (HBV) infection by induction of apoptosis by inhibiting cellular inhibitor of apoptosis proteins (cIAPs) has been reported in the literature (Alonso et al., 2017 ; Ebert et al., 2015). The second antiviral lead compound i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Birinapant is currently an investigational drug for a variety of cancers, and it is to be noted that the activity of birinapant to induce apoptosis can vary among different cell types, and cancer cells (or cell lines derived from cancer cells) are likely to be more sensitive to the drug ( Fulda and Vucic, 2012 ; Bai et al, 2014 ). However, it is noteworthy that birinapant is also currently being investigated for its use in the treatment of chronic HBV infection ( Ebert et al, 2015 ), and a phase II clinical trial is currently ongoing ( Alonso et al, 2017 ). Regarding the utility of birinapant for HIV-1 infection, especially to cure HIV-1, Pache et al (2015) reported that certain Smac mimetics reactivated latent HIV-1-infected cells and raised their HIV-1 mRNA expression ( Pache et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic HBV infections are currently treated with pegylated interferon-α, which increases immune activity, and/or with nucleoside analogs that block the RT domain from replicating viral DNA. Both of these main classes of drugs achieve hepatitis B surface antigen (HBsAg) loss only rarely; interferon is poorly tolerated, and nucleoside analogs are administered for life to achieve a reduction in viral load [2][3][4].…”
Section: Of 19mentioning
confidence: 99%
“…Although several hundred million people in the world are infected by HBV, an effective vaccine exists, as well as non-curative treatment [1]. Current antiviral drugs, except immunomodulatory drugs such as pegylated interferon α and thymalfasin, are all directed against the HBV polymerase (Pol) [2][3][4], though therapeutics for novel targets are in development [5]. Although there is no small animal model capable of infection with human HBV, informative studies have been performed using related HBV species that infect avian and mammalian hosts, such as duck HBV (DHBV) and woodchuck HBV [6].…”
Section: Introductionmentioning
confidence: 99%